Pengembangan Media Video Animasi Berbasis Powtoon untuk Meningkatkan Critical Thinking Peserta Didik Sekolah Dasar - Wulandari, Dewi Sri Rizki; Firdaus, Rangga; Yunarti, Tina; Nurhanurawati, Nurhanurawati (Mitra PGMI: Jurnal Kependidikan MI, 2024)
This research aims to develop Powtoon-based animation videos to improve students' critical thinking. The research method uses ADDIE which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The research sample was class IV A as the experimental class and IV B as the control class. The results of the study include the feasibility, practicality, and effectiveness of the product. The feasibility of the product is considered valid based on the validation results, with an average Aiken index of 0.808 for material, 0.958 for language, and 0.608 for media. The practicality of the product was seen from the responses of educators (90%) and students (89%), both of which were interpreted as very practical. The effectiveness of the product was measured through a comparison of the improvement of critical thinking skills between the experimental and control classes. The results show that the experimental class has an effect size value of 0.798, which is interpreted as high. This proves that the use of Powtoon-based animated videos significantly improves critical thinking skills compared to those who do not use the product.